Dose–response relationship between physical activity and cardiometabolic risk in obese children and adolescents: A pre-post quasi-experimental study - Chen, Zekai; Zhu, Lin (Frontiers in Physiology, 2023)
Objective: This study aims to explore the dose-response relationship between the daily duration of moderate to vigorous physical activity (MVPA) and the improvement of cardiometabolic risk (CMR) indicators in obese children and adolescents. Methods: Seventy-seven obese children and adolescents aged 10–17 years were randomly recruited for a 4-week exercise intervention in a closed camp during 2019 to 2021, physical activity was monitored by ActiGraph GT3X+ to obtain daily MVPA duration, and the improvement of CMR indicators were reflected by the changes () of waist circumference (WC), systolic blood pressure (SBP), diastolic blood pressure (DBP), total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), fasting insulin (FINS), fasting plasma glucose (FPG), and homeostasis model assessment of insulin resistance (HOMA-IR) before and after the intervention, calculated as “+indicator” = values after intervention – values before intervention. The groups were divided into different doses of Q1 Q3 according to the daily MVPA duration from low to high. The differences in the improvement of different dose groups were compared by one-way analysis of covariance (ANCOVA), and the dose-response relationship between MVPA duration and CMR indicators improvement was analyzed by linear regression and piecewise regression. The nonlinear relationship was analyzed by restricted cubic spline (RCS). Results: (1) Compared with indicators before the intervention, WC, SBP, DBP, TC, TG, HDL-C, LDL-C, FINS, and HOMA-IR were significantly lower after the intervention (P value<0.05). (2) The dose-response relationship between MVPA and LDL-C improvement was non-linear (P-Nonlinear<0.05). When MVPA > 77.1min/day, LDL-C further decreased with the increase of MVPA duration [β=-0.013, 95% confidence interval (CI): -0.013, -0.005], and when MVPA ≤ 77.1min/day, increasing the MVPA duration did not increase the improvement of LDL-C. Conclusion: There was a nonlinear dose-response relationship between the daily MVPA duration and LDL-C improvement in obese children and adolescents. In order to obtain more significant improvement in LDL-C through increased MVPA duration, MVPA duration should be higher than 77.1 min/day.